Abnormal Pap Smear and Diagnosis of High-Grade Vaginal Intraepithelial Neoplasia: A Retrospective Cohort Study. Issue 42 (October 2015) - Sopracordevole, Francesco; Mancioli, Francesca; Clemente, Nicolò; De Piero, Giovanni; Buttignol, Monica; Giorda, Giorgio; Ciavattini, Andrea
Abstract : Abstract: The aim of this study was to analyze the correlation between the first diagnosis of high-grade Vaginal Intraepithelial Neoplasia (HG-VaIN: VaIN 2–VaIN 3) and the cytological abnormalities on the referral pap smear. All the women with histological diagnosis of HG-VaIN consecutively referred to the Gynecological Oncology Unit of the Aviano National Cancer Institute (Aviano, Italy) from January 1991 to April 2014 and with a pap smear performed in the 3 months before the diagnosis were considered, and an observational cohort study was performed. A total of 87 women with diagnosis of HG-VaIN were identified. Major cytological abnormalities (HSIL and ASC-H) on the referral pap smear were significantly more frequent than lesser abnormalities (ASC-US and LSIL) in postmenopausal women (64.9% vs 36.7%, P = 0 .02) and in women with a previous diagnosis of HPV-related cervical preinvasive or invasive lesions (70.5% vs 39.5%, P = 0 .01). Diagnosis of VaIN 3 was preceded by major cytological abnormalities in most of the cases (72.7% vs 27.3%, P < 0 .001). The diagnosis of HG-VaIN can be preceded by different abnormalities on referral pap smear. Major abnormalities are usually reported in postmenopausal women and in women with previous cervical HPV-related disease. However, ASC-US or LSIL do not exclude HG-VaIN, especially VaIN2. An accurate examination of the whole vaginal walls (or vaginal vault) must be performed in all the women who underwent colposcopy for an abnormal pap smear, and a biopsy of all suspicious areas is mandatory.